Analysis of different choroidal stratification thickness under macular fovea in patients with early graves ophthalmopathy - Dan Zhang (Guoji Yanke Zazhi, 2019)
AIM: To compare the difference of choroidal delamination thickness in macular fovea between patients with early active Graves ophthalmopathy and healthy subjects by optical coherence tomography(OCT)enhanced deep imaging. METHODS:From December 2017 to May 2019, patients with early active Graves ophthalmopathy diagnosed in our hospital(GO group)and 31 patients(62 eyes)with age and sex matched healthy physical examination(control group)were selected. Diopter, best-corrected visual acuity(BCVA), intraocular pressure, exophthalmos, EDI-OCT and other examinations were performed on all the subjects. The differences of macular central concave choroidal thickness(SFCT), choroidal macrovascular layer thickness(LCVT)and choroidal capillary layer/middle vascular layer thickness(MCVT)between the two groups were compared. RESULTS: There was no significant difference in equivalent spherical lens power, BCVA and eye axis between the two groups. However, the IOP(17.22±2.67mmHg), exophthalmos(15.44±0.92mm), SFCT(315.79±14.99μm), LCVT(234.66±14.90μm)in GO group were significantly higher than those in control group(13.35±1.54mmHg, 12.90±1.00mm, 239.00±12.67μm, 159.16±13.30μm)(all PSymbol|@@0.05), but there was no significant difference in MCVT between the two groups(81.13±7.46μm vs 80.13±7.63μm, P>0.05). CONCLUSION: SFCT and LCVT in patients with early active Graves ophthalmopathy are thickened, and MCVT has no obvious change, suggesting that EDI-OCT measurement of SFCT and LCVT has certain reference value for evaluating early active Graves ophthalmopathy.